2019
DOI: 10.1111/acem.13709
|View full text |Cite
|
Sign up to set email alerts
|

Do High‐sensitivity Troponin and Natriuretic Peptide Predict Death or Serious Cardiac Outcomes After Syncope?

Abstract: Objectives: An estimated 1.2 million annual emergency department (ED) visits for syncope/near syncope occur in the United States. Cardiac biomarkers are frequently obtained during the ED evaluation, but the prognostic value of index high-sensitivity troponin (hscTnT) and natriuretic peptide (NT-proBNP) are unclear. The objective of this study was to determine if hscTnT and NT-proBNP drawn in the ED are independently associated with 30-day death/serious cardiac outcomes in adult patients presenting with syncope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Diagnostic imaging (such as computer tomography angiography or echocardiography) and laboratory tests (such as routine blood hematology, biochemistry) have low diagnostic yield and should not be routinely used for syncope assessment. Cardiac damage biomarkers such as troponin and brain natriuretic peptide (BNP) have proven valuable in emergency presentations offering help to busy emergency physicians to select those patients requiring hospitalization (Clark et al, 2019;du Fay de Lavallaz et al, 2019). Some still frequently employed testing should now be considered inappropriate due to lack of diagnostic yield in syncope patients, notably EEG and brain imaging.…”
Section: Why and How To Identify High-risk Syncope?mentioning
confidence: 99%
“…Diagnostic imaging (such as computer tomography angiography or echocardiography) and laboratory tests (such as routine blood hematology, biochemistry) have low diagnostic yield and should not be routinely used for syncope assessment. Cardiac damage biomarkers such as troponin and brain natriuretic peptide (BNP) have proven valuable in emergency presentations offering help to busy emergency physicians to select those patients requiring hospitalization (Clark et al, 2019;du Fay de Lavallaz et al, 2019). Some still frequently employed testing should now be considered inappropriate due to lack of diagnostic yield in syncope patients, notably EEG and brain imaging.…”
Section: Why and How To Identify High-risk Syncope?mentioning
confidence: 99%
“…[9,10] However, with the introduction of highly sensitive troponin kits, studies conducted in recent years have found a relationship between high-sensitivity troponin and syncope in terms of detecting poor outcomes in the patient group. [11–14] In our study, the cutoff value for hs-cTnT determination was determined as 7.3. Compared to previous studies, a higher diagnostic value of troponin was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic inhaled gases such as halogens and carbon monoxide may cause cardiac hypertrophy on one hand and inhalation of other gases such as nitric oxide and hydrogen may help reverse hypertrophy caused by other agents/mechanisms 39,40 . Persistent increase in troponin and NT-proBNP is a great prognostic value for predicting serious cardiac outcomes in patients 41,42 . These key circulating heart-specific biomarkers (brain natriuretic protein, BNP and troponin) were elevated at both 14 and 28 days.…”
Section: Discussionmentioning
confidence: 99%